Student teachers' decision-making about working at Masters level on their PGCE courses - Brook, Victoria (2012)
Decisions about different educational pathways have been linked extensively with inequality of outcome and explaining this link has been a focus of much recent research. The emphasis for such research has largely been at key transition points such as secondary school choice and entry to Higher Education. A key question has been the extent to which decisions are influenced by the structuring effects of social class and cultural background or individual agency. This study examines the educational decision-making of graduate student teachers in relation to whether or not to take Masters level credits on courses of Initial Teacher Education. It uses a mixed methods case study approach to collect data from the staff, student teachers and documentation within an Initial Teacher Education department of a Higher Education Institution. The study draws upon a Bourdieuian theoretical perspective to understand the individual nature of the decision-making process and how it led to patterns of inequality. The process of decision-making is considered through the interrelated dimensions of agency, contexts and values. The study reveals that the student teachers' decision-making was multifaceted, and demonstrates the different ways in which important factors were linked and dependent on the overlapping influences of socio-cultural background. The majority of student teachers decided not to take Masters level credits, in many cases seeing the Masters level pathway as too risky. The major influential factors included concerns about time and workload and fear of failure with perceptions of level of academic skills contributing towards this. For some student teachers the perceived value of Masters level for teaching and aspirations for personal progression were also important factors. The study also demonstrates that inequitable patterns of outcome related to student teachers' characteristics could be aggregated from individual decisionmaking. The study draws the conclusion that the introduction of differentiated educational pathways should be accompanied by careful monitoring to ensure that the aims of widening participation are not compromised. Recommendations are made for the types of support that could accompany this particular case of educational decision-making and lessen any stratifying effects. These recommendations could be transferrable to other situations where decisions have to be made about a particular educational pathway.